Pedagogical Practices and Learner Performance: A Qualitative Study - Guzman, Grace (Azal Arts and Humanities, 2025)
This qualitative study explored pedagogical practices and their influence on learner performance at C.J. Torre Elementary School. Using a descriptive qualitative research design, the study examined teachers’ instructional strategies, classroom practices, and learners’ experiences to understand how pedagogy shapes engagement, comprehension, and academic performance. Data were collected through in-depth interviews, classroom observations, and document analysis involving selected teachers and pupils. Thematic analysis was employed to identify emerging patterns and themes. Findings revealed that learner-centered instruction, contextualized teaching, and differentiated practices significantly enhanced learner engagement and understanding. Teachers actively involved pupils through interactive activities and connected lessons to real-life experiences, making learning meaningful and relevant. Differentiated instruction addressed varied learner abilities, enabling inclusive participation and improved performance. Despite challenges such as limited resources and time constraints, teachers demonstrated adaptive practices by improvising materials and modifying instruction to meet learners’ needs. The study concludes that effective and responsive pedagogical practices play a crucial role in improving learner performance at the elementary level. The findings provide insights for instructional improvement, school leadership, and curriculum development aimed at fostering inclusive and meaningful learning experiences.